Boost Converter with Optimized Pi Controller Design for Grid Tied PV Based Electric Vehicle - AranGlenn J. (International Journal of Electrical Power and Machine Systems, 2025)
The growing demand of clean energy along with the depletion of fossil fuel usage have paved the way for electric vehicles (EV) to emerge as a significant alternative in automobile sector. Reduction of air pollution and reliance of fossil fuels thereby improving energy security are termed as the primary goals of EV. The adopting of EV facilitates emission free transportation and addresses the environmental crisis caused due to climatic changes and pollution. The integration of EVs with renewable energy sources (RES) supports decarbonized energy production contributing to cleaner environment. The abundant availability in nature enables the solar system to be widely used for the integration with EVs. The intermittent nature of photovoltaic systems (PV) is solved by the inclusion of efficient DC-DC converters along with grid supply which in turn enables the constant power flow in the charging system. The focus of this paper is to develop an effective charging system for EV which contributes a crucial role in achieving a pollution free future. A novel Trans Z-source Luo converter is used to enhance the PV output voltage thereby lessening the number of PV panels used. The proposed converter exhibits the benefits like excellent efficiency, lesser voltage stress and high conversion range. The operation of the proposed converter is regulated with the aid of Lion Grey Wolf Optimized Proportional Integral (LGWO-PI) controller which significantly strengthens the converter operation in terms of settling time, total harmonic distortion (THD) and peak overshoot. The obtained converter output energizes the Brushless Direct Current Motor (BLDC) motor of EV after its conversion to AC form by a Voltage Source Inverter (VSI). A conventional PI controller is used for the effective speed control of BLDC motor. At times of power unavailability from PV systems, a VSI fed grid is used to energize the BLDC motor. Overall, the complete charging setup provides a constant power supply for EVs. The presented work is simulated using MATLAB and the outputs indicate the enhanced functioning of the charging system. Comparisons are carried out with existing converters and control approaches in which the proposed system delivers a reduced THD of 2.1% and an optimal efficiency of 97.6%.
Keywords: BLDC Motor; LGWO-PI controller; PI controller; PV system; boost converter; single phase VSI; three phase VSI, EV charging